(untitled) (Fiep Bulletin - online, 2011)
Introduction: The increasing prevalence of chronic-degenerative diseases requires risk factors’ identification in the diverse population, especially on workers. Objectives: The objective was to describe the workers’ health profile in the diverse business, scoping physical fitness, nutrition and risk factors. Methodology: It is a descriptive-exploratory survey, based on the evaluation of 400 formal workers in Santa Cruz do sul, in 2008 and 2009, from both gender and in distinct working business. Anthropometric data were gathered: body mass index (BMI = kg/m2), waist/hip ratio (WHR), waist circumference (WC) and body fat percentage (BF%); muscle-skeletal health: sit and reach tests (SRT), rotator cuff flexibility (RC), abdominal tests (AbT) and press-up (an exercise in which the body is alternately raised from and lowered to the floor by the arms only) in dynamic muscle endurance; the cardio respiratory fitness was estimated by Rockport test (VO2) and the cardiovascular by resting blood pressure (BP). Results: The individuals’ results demonstrate 51,3% with body mass index ≥ 25 kg/m2, in G, 32,6% rated "good and above average" and 44,8% of women with "below average and poor"; in the Waist-hip ratio "low or moderate risk" in 75,8%; and, in waist circumference "normal risk" in 74,5%. The flexibility index is "below average and low condition" in the right rotator cuff (69,3%) and left (60,3%), and 63,5% in the sit-and -reach test, as well as in the abdominal test 72,3%, the muscular dynamic endurance in the press-up exercise 60,6% from "average to excellent". The blood pressure test presented "normal" rate in 62,5%, and VO2 with "excellent and good" results in 64,6% of the evaluated individuals. Conclusion: Although the results were favorable in a few variables, the low rates in flexibility and abdominal tests (AbT) are negative, requiring mores attention in these aspects.